Improved dark fermentation of cane molasses in mesophilic and thermophilic anaerobic fluidized bed reactors by selecting operational conditions. (13th July 2020) - Ferreira, Tiago B.; Rego, Gabriel C.; Ramos, Lucas R.; de Menezes, Camila A.; Silva, Edson L.
Summary: Sugarcane molasses is a carbohydrate‐rich carbon source with potential to develop the biorefinery model in the sugarcane industry. Two of the most well‐known renewable products from the dark fermentation of cane molasses are succinic acid and biohydrogen, with both having valuable applications in different industries. However, the continuous dark fermentation of cane molasses is a process regulated by many operational conditions, like reactor temperature and hydraulic retention time. It is important to control these conditions to shift metabolic pathways in order to increase production rates and yields. Thus, this research evaluates the response of mesophilic and thermophilic dark fermentation of cane molasses by mixed culture on hydrogen and succinic acid generation in fluidized bed reactors by changing the hydraulic retention time (8, 6, 4, 2, and 1 hour). In the thermophilic reactor (55°C), higher hydraulic retention times (from 8 to 4 hours) favored the succinate production (molar fractions between 75.0% and 81.4%). Similarly, in the mesophilic reactor (30°C), the molar fractions of succinate were 45.5% at the hydraulic retention time of 8 hours and 74.7% at 6 hours. The reduction of the hydraulic retention time to 1 hour decreased the succinic acid concentration to undetectable values and increased the hydrogen yield in both reactors. The lower hydraulic retention time also enhanced the hydrogen productivity to 171.1 mL/Lbed ·h in the mesophilic reactor and to 303.4 mL/Lbed ·h in the thermophilic reactor. These values were coincident with the predominant production of butyric and acetic acids. All of these points to the fact that the hydraulic retention time is an efficient parameter to control and select the production of hydrogen or succinic acid by mixed cultures under different temperatures. Abstract : To our knowledge, this is the first study to compare mesophilic and thermophilic conditions for the continuous dark fermentation of sugarcane molasses in anaerobic fluidized bed reactors using different mixed cultures. Based on the results observed, the variation of hydraulic retention time can select the microbial populations and the main metabolic pathways between succinic acid and hydrogen production routes in high‐rate mesophilic and thermophilic reactors. This enables the adoption of precise operational conditions depending on the targeted product.